NHC-catalyzed activation of aldehydes for asymmetric reactions - Chen, Xingkuan (2014)
My study is mainly focused on the N-heterocyclic carbene catalytic activation of special aldehydes reactions. In this thesis, cis-enals and α-branched indole 3-carboxaldehydes were explored. cis-Enals with carbene could form cis-homoenolate intermediate which offer different stereo selectivities and distinct reactivity patterns. α-Branched indole 3-carboxaldehydes react with carbene to produce ortho-quinodimethane intermediates which undergo highly enantioselective [4+2] cycloaddition reaction. The thesis is divided into three chapters: Chapter I contains a brief introduction on organocatalysis and NHC catalysis. Chapter II describes the first example of N-heterocyclic carbene catalyzed benzilic sp3 C-H bond functionazation. In this part, we devoloped a NHC catalyzed activation of sp3 carbon of α-branched indole 3-carboxaldehydes to produce ortho-quinodimethane intermediates that further undergo highly enantioselective formal [4+2] cycloaddition with trifluoromethyl ketones and isatins to give multicyclic spiroyclic lactones. Chapter III contains the first successful employment of cis-enals in NHC-mediated cis-homoenolate generations. We have shown that cis-enals can offer different stereo-selectivities and somewhat surprisingly distinct reactivity patterns.